Comparison of Sutureless Hemorrhoidectomy versus Conventional Hemorrhoidectomy in the Case of Large Internal Hemorrhoids - Jalil, Mohammad; Mureed, Irfan; Rehman, Shams Ur; Ishrat, Haseeb; Aslam Javaid, Mian Adnan (Biological and Clinical Sciences Research Journal, 2025)
Hemorrhoidal disease is a common anorectal condition with significant morbidity, particularly in advanced grades (III–IV) requiring surgery. Conventional hemorrhoidectomy, though effective, is associated with longer operative times, higher blood loss, postoperative pain, and prolonged hospital stay. Sutureless hemorrhoidectomy techniques have been introduced to reduce these drawbacks and improve recovery. Objective: To compare operative parameters and postoperative outcomes of sutureless hemorrhoidectomy versus conventional hemorrhoidectomy in patients with large internal hemorrhoids. Methods: This randomized controlled trial was conducted at the Department of General Surgery, Bahawal Victoria Hospital, Bahawalpur, Pakistan, from 16th February to 16th May 2025. Sixty patients aged 20–70 years with grade III or IV internal hemorrhoids (≥4 cm) were randomized equally into two groups: Group A (sutureless) and Group B (conventional). Outcomes measured included operative time, intraoperative blood loss, pain score at 24 hours (using the Visual Analog Scale, or VAS), hospital stay, and recurrence at 3 months. Data were analyzed using SPSS version 25.0, with independent t-tests and chi-square tests applied. A p-value of ≤ 0.05 was considered statistically significant. Results: Baseline demographic and clinical characteristics were comparable between groups (mean age 44.2 ± 11.3 years; 65% male). The sutureless group had significantly shorter operative time (27.4 ± 6.5 vs. 38.9 ± 7.8 minutes, p < 0.001), less blood loss (48.2 ± 13.7 vs. 68.6 ± 18.9 ml, p < 0.001), lower 24-hour pain scores (3.8 ± 1.2 vs. 6.1 ± 1.5, p < 0.001), and shorter hospital stay (1.3 ± 0.5 vs. 2.4 ± 0.7 days, p < 0.001). At 3-month follow-up, recurrence was observed in 1 patient (3.3%) in the conventional group and none in the sutureless group. Conclusion: Sutureless hemorrhoidectomy offers significant advantages over conventional hemorrhoidectomy in terms of reduced operative time, intraoperative bleeding, postoperative pain, and hospital stay, with comparable safety and low recurrence. It represents a safe, effective, and patient-friendly alternative for managing large internal hemorrhoids in the Pakistani population.